Sodium–glucose cotransporter 2 inhibitors ameliorate glutathione cysteine ligase modifier-mediated oxidative stress and subsequent ferroptosis in proximal tubules of diabetic kidney disease - Yi-Chun Tsai; Jiun-Chi Huang; Ping-Shaou Yu; Mei-Chuan Kuo; Ling-Yu Wu; Wei-An Chang; Shang-Jyh Hwang; Ya-Ling Hsu (Redox Report)
Objectives Diabetic kidney disease (DKD) is a major cause of end-stage kidney disease. The precise molecular mechanism of ferroptosis, an iron-dependent and non-apoptotic form of regulated cell death, remains poorly understood in DKD, as does the impact of sodium-glucose cotransporter 2 inhibitors (SGLT2i) on ferroptosis-mediated DKD.Methods This study used bulk RNA sequencing, in vitro and in vivo models, and human kidney samples to explore the molecular mechanisms involved in oxidative stress and ferroptosis in the proximal tubule (PT) of DKD.Results High glucose (HG) induced features of ferroptosis in HK-2 cells. Transcriptome analysis of primary PT cells from diabetic patients indicated that glutathione cysteine ligase modifier (GCLM) subunit is involved in ferroptosis. Immunohistochemical staining revealed that db/db mice and diabetic patients had lower glutathione peroxidase 4 and GCLM expression in the PT. Suppression of GCLM enhanced ferroptosis, whereas GCLM overexpression mitigated HG-induced ferroptosis in HK-2 cells. Antioxidants reduced oxidative stress and ferroptosis in both in vitro and in vivo models of DKD. Furthermore, SGLT2i attenuated PT ferroptosis in these models and improved DKD by increasing GCLM expression.Conclusion SGLT2i reduced ferroptosis in PT by boosting GCLM expression, thereby slowing DKD progression, revealing that GCLM has the potential against DKD.